A pilot scale study of low dissolved oxygen oxic-anoxic process for biological nitrogen removal from tropical sewage / Leong Chew Lee - Leong , Chew Lee (2024)
Complying with nitrogen effluent discharge limits in domestic sewage treatment comes with high energy and chemical costs. Conventional biological nitrogen removal (BNR) process, which maintains high dissolved oxygen (DO) concentrations (>2 mg/L), often consumes half of the total plant’s energy for aeration. Stakeholders in the sewage industry are seeking ways to improve energy sustainability. Low-DO oxic-anoxic (low- DO OA) meets the criteria as a simpler, cost-effective and efficient biological treatment process due to its operation at low DO level (<1 mg/L). The lab-scale low-DO OA reactor completely removed ammoniacal-nitrogen (NH4-N) and produced low effluent nitrate-nitrogen (NO3-N) when treating local sewage. However, the feasibility of the low-DO OA process has yet to be validated at a scaled-up level for nitrogen removal. This project aimed to evaluate the feasibility of an on-site pilot-scale low-DO OA process in treating domestic sewage with low chemical oxygen demand-to-nitrogen ratio (COD/N) in tropical climate. Despite the low COD/N influent sewage, further denitrification experiments revealed that slowly biodegradable COD (sbCOD), predominantly present in particulate settleable solids (PSS) in domestic wastewater, can effectively support nitrogen removal efficiency. Nitrification batch tests demonstrated that operating the BNR at low DO concentrations is feasible. Nitrifiers from low DO sludge samples have a higher oxygen affinity with a lower half-saturation constant (